Blue crimes and ocean harmscapes: strategies for tackling Transnational Maritime Environmental Crimes in the Global South - Hübschle, Annette; Lindley, Jade (Frontiers in Conservation Science, 2024)
Transnational Maritime Environmental Crimes (TMEC) represent a burgeoning threat to marine ecosystems, biodiversity, and the socio-economic sustainability of coastal communities, especially in the Global South. By examining the impacts of illegal, unreported, and unregulated (IUU) fishing in the Philippines and sea cucumber trafficking in the Seychelles, the paper underscores the urgent need for innovative and inclusive strategies. We approach these issues through a comprehensive framework that integrates the carrot-and-stick concept, whole-of-society perspectives, and southern blue criminology principles. The carrot-and-stick methodology balances incentives for compliance with penalties for violations, fostering behavioral change among states and individuals involved in TMEC. Whole-of-society perspectives emphasize the inclusion of all stakeholders-governments, corporations, civil society, and local communities-in designing and implementing regulatory measures. Southern blue criminology provides a critical lens to tailor governance frameworks to the unique socio-economic contexts of the Global South. This integrated approach aims to create resilient, sustainable and gender-sensitive solutions, promoting global cooperation in the fight against TMEC. By leveraging incentives, engaging stakeholders, and prioritizing socio-ecological considerations, we can protect marine environments and support the livelihoods of coastal communities, aligning with the goals of Sustainable Development Goal 14.